On the influence of sugarcane bagasse ashes as a partial replacement of cement in compressive strength of mortars - Romildo Alves Berenguer; Paulo Helene; Fernando Artur Nogueira Silva; Sandro Marden Torres; Eliana Cristina Barreto Monteiro; Antônio Acacio de Melo Neto (Revista ALCONPAT, 2018)
This paper presents an experimental program objectifying at investigating the potential of the use of sugarcane bagasse ash as a partial replacement of cement in the production of mortars. Sugarcane bagasse ashes from two origins were studied - one from sugarcane industry directly and other from pizzerias that uses this material replacing the wood in their ovens. The methodology followed the characterization of the material, where it was carried out through laboratory tests using X-ray diffraction (XRD) and X-ray fluorescence (WDXRF) and initial tests for the ideal quantification of cement substitution by residues. Results obtained indicated that both residues exhibited pozolanic features presenting about 60% of amorphous material in their composition and compressive strength tests at different ages showed satisfactory results. Concluding that residues played an important role in increasing short and long term compressive strengths.